2018
DOI: 10.3390/su10020455
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Sustainable Transportation Operations through Corridor Management: A Simulation Gaming Approach

Abstract: Synchromodality is described as a network of well-synchronised and interconnected transportation modes. One of the most important advantages of synchromodality is the development of a sustainable transportation system. Given the numerous stakeholders and network interdependencies within freight transport corridors, achieving efficient coordination and management is complex. In this paper, we regard information exchange as one of the main enablers of collaboration between the infrastructure managers. We develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
(36 reference statements)
0
15
0
1
Order By: Relevance
“…Serious games represent an interactive and efficient instrument for learning, decision-making, and awareness building and they are an effective tool for simulating dynamic and complex systems, such as transport and logistics systems [35,36]. While the sector has successfully implemented game-based approaches to address several challenges already (see e.g., [44,45,63,64]), the question of innovation implementation has not yet been addressed thoroughly through a game-based approach. Below, we explain how the two games, based on the two illustrated cases, have been designed in order to fill this gap.…”
Section: Development Of the Serious Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious games represent an interactive and efficient instrument for learning, decision-making, and awareness building and they are an effective tool for simulating dynamic and complex systems, such as transport and logistics systems [35,36]. While the sector has successfully implemented game-based approaches to address several challenges already (see e.g., [44,45,63,64]), the question of innovation implementation has not yet been addressed thoroughly through a game-based approach. Below, we explain how the two games, based on the two illustrated cases, have been designed in order to fill this gap.…”
Section: Development Of the Serious Gamesmentioning
confidence: 99%
“…Focusing on the Dutch railway system, Van den Hoogen and Meijer [44], found that simulation gaming can contribute to the coordinated planning of innovation implementation. Kurapati et al [45], examined how simulation games can be used to foster sustainability in transportation operations through synchromodal corridor management. The authors developed a digital simulation game which was tested in game sessions with experts in The Netherlands.…”
mentioning
confidence: 99%
“…Several perspectives on how to validate (or evaluate) games exist (e.g., [50][51][52]). In this work, we follow the perspective that this activity could be assimilated to the "confirmation through the provision of objective evidence that the requirements for a specific intended use or application of a system have been fulfilled" [53], where the term "system" refers to the game.…”
Section: Knowledge Acquisition Experimentsmentioning
confidence: 99%
“…Simulation gaming is an increasingly accepted research method to study complex systems (Kurapati et al, 2018). Simulation games can be described as experimental, rule-based, interactive and social organization, constituted by the players themselves, who learn by taking actions and by experiencing their effects through feedback mechanisms within the game (Mayer, 2009;Lukosch et al, 2018).…”
Section: Simulation Gamingmentioning
confidence: 99%